Novel Isoquinoline Alkaloid Litcubanine A - A Potential Anti-Inflammatory Candidate - Xia, Huan; Liu, Yitong; Xia, Guiyang; Liu, Yi; Lin, Sheng; Guo, Lijia (Frontiers in Immunology, 2021)
Macrophages play a critical role in innate and adaptive immunity, and the regulation of macrophage function in inflammatory disease treatment has been widely studied. Litsea cubeba is an important Chinese medicinal plant used for the treatment of inflammatory diseases. However, the inflammatory bioactive ingredients in L. cubeba and underlying molecular mechanisms are poorly understood. Herein, we first obtained and elucidated a novel isoquinoline alkaloid, Litcubanine A (LA), from L. cubeba. An in vitro study indicated that LA could significantly inhibit LPS-induced activation of inflammatory macrophages via the NF-κB pathway, leading to the decrease of inflammatory factors including iNOS, TNF-α, and IL-1β. Moreover, LA showed an inhibiting effect on the expression of NO in macrophages by directly binding to iNOS protein. Molecular simulation docking also demonstrated that active LA created an interaction with GLU 89 and GLU 371 residues of iNOS via hydrogen bonding derived from the N→O group, revealing its highly selective inhibition toward iNOS. By using the IκK inhibitor and iNOS inhibitor, these two regulatory targets of LA on inflammatory macrophages were verified in vitro. Finally, by using a caudal fin resection model in zebrafish larvae, and the skin wound healing model in mice, we proved in vivo that LA down-regulated the secretion of local inflammatory factors by inhibiting macrophage recruitment and activation at the early stage of the injury. Collectively, our study demonstrated that the novel isoquinoline alkaloid LA suppresses LPS-induced activation of inflammatory macrophages by modulating the NF-κB pathway, suggesting that inflammatory macrophage activation pathway is an effective target for inflammation treatment, and LA is a new pharmacophore for the development of novel and effective anti-inflammatory agents to regulate local macrophages.